CLAIMS OF FACT IN THE ARGUMENTATION ON ISSUES OF ISLAMIC COUNTRIES IN NEWSWEEK INTERNATIONAL MAGAZINE - Rohmani Nur Indah (Kajian Linguistik dan Sastra, 2015)
Argumentation is basically the art of influencing others through the medium of reasoned discourse. This research deals with how rhetorical strategies are employed in reasoned discourses especially those written in mass media read by international readers. The reasoning must be based on the principles of claim presentation. The evidences used to support the claim become significant as they portray issues in Islamic countries. Employing descriptive qualitative design, this research examines the writer’s opinion column and world view section in Newsweek International Magazine published currently. The analysis is made on the claim, method of defense as well as the rhetorical strategies employed in organizing the ideas of the argument.